Association between red cell distribution width to albumin ratio and clinical outcomes in elderly patients with sepsis: a cohort study - An, Li; Fu, Zhiqing; Chen, Zhenhong; Xiong, Xiaomiao; Li, Minsheng; Lu, Limei; Zhang, Zhijian; Li, Shan (Frontiers in Nutrition, 2025)
BackgroundThis study investigates the association between red cell distribution width to albumin ratio (RAR) and clinical outcomes in elderly sepsis patients.MethodsThis study investigates the association between red cell distribution width to albumin ratio (RAR) and clinical outcomes in elderly sepsis patients. Methods: Using the eICU-CRD (2014–2015), 5,976 sepsis patients aged≥60 years were stratified into RAR quartiles at ICU admission: Q1 (≤5.28), Q2 (5.29–6.37), Q3 (6.38–7.87), and Q4 (7.88–15.0), with Q1 as the reference category. The primary outcome was 28-day hospital mortality, while secondary outcomes included ICU mortality, 90-day hospital mortality, and lengths of ICU and hospital stays. Multivariable regression analysis and spline curves from the generalized additive model were applied to assess the association between RAR and clinical outcomes. Kaplan–Meier survival analysis illustrated cumulative hospital mortality across RAR quartiles.ResultsThe 28-day hospital, ICU, and 90-day hospital mortality were 17.4, 10.9, 17.8%, respectively, with ICU and hospital stays of 2.9 (1.8–5.1) and 7.1 (4.6–11.7) days. Compared to Q1, Q4 exhibited significantly increased risks of 28-day hospital mortality (adjusted odds ratio [OR]: 2.95, 95% confidence interval [CI]: 2.28–3.80), ICU mortality (adjusted OR: 2.06, 95% CI: 1.52–2.78), 90-day hospital mortality (adjusted OR: 3.03, 95% CI: 2.35–3.90), and prolonged ICU (β: 0.89, 95% CI: 0.42, 1.36) and hospital stays (β: 1.64, 95% CI: 0.93, 2.36). Generalized additive model revealed linear relationship between RAR and mortality. Kaplan–Meier survival analysis demonstrated higher mortality with elevated RAR quartiles.ConclusionElevated baseline RAR is independently associated with adverse clinical outcomes in elderly sepsis patients, suggesting it may be a valuable tool for early risk stratification and personalized therapeutic interventions.